Vagus nerve preservation and double-flap technique in laparoscopic proximal gastrectomy - Sun, Ke-Kang; Shen, Xiao-Jun; Hua, Peng; Zhang, Yi-Fan; Wu, Yong-You (Frontiers in Surgery, 2025)
ObjectivesLaparoscopic proximal gastrectomy has been a common treatment strategy for proximal early gastric cancer. The conventional double-flap technique (DFT), also called Kamikawa method, does not require vagus nerve preservation, which is precisely crucial to maintain quality of life and prevent postoperative reflux esophagitis.MethodsA single-center retrospective analysis was conducted on 37 gastric cancer patients undergoing laparoscopic proximal gastrectomy with vagus nerve preservation and double-flap technique. The hepatic and celiac branches were both preserved. A seromuscular double-flap was created through the auxiliary incision, and the anastomosis between the oesophagus and the remnant stomach was performed under laparoscopy.Results2.7% of the patients suffered from slight anastomotic stricture but subsequently recovered after conservative treatment. No patients experienced anastomotic bleeding or leakage. No food residue and GERD (Los Angeles classification grade B or higher) were observed in any patients 6 months later. Ultrasonography showed that the gallbladder contractile function was normal in all patients.ConclusionAlthough long-term follow-up and a larger number of patients are required to evaluate the functional outcomes, our technique provides a minimally invasive surgical option for proximal early gastric cancer, especially in the prevention of postoperative reflux esophagitis.